Konstruksi Narasi Surga: Analisis Wacana Kritis Berita Janji Kampanye Calon Bupati Mesuji - Ghivari, Raditya Wilmar; Kosasih, Aceng (Icon: Islamic Communication and Contemporary Media Studies, 2024)
Political discourse, especially those using religious narratives such as ‘heaven’, plays an important role in shaping perceptions and legitimacy of regent candidates in Mesuji, and can influence voter support through emotional communication strategies. Critical discourse analysis is needed to understand how language and social context interact, as well as their impact on collective identity and social polarisation. This research aims to explore religious values in political campaigns and the role of digital media in the dissemination of such narratives. This research analyses the construction of the ‘heaven’ narrative in the campaign promises of Mesuji regent candidates through CNN Indonesia's digital media coverage, using a descriptive qualitative method, with linguistic and religious approaches. By applying Teun A. van Dijk's critical discourse analysis theory, this research explores the text structure and social context that influence the presentation of the narrative, and collects data from various primary and secondary sources. The results show that the discourse presented reflects the power and ideologies that exist in society, providing deep insight into how the narrative is shaped and accepted.